(untitled) (Forum Agribisnis, 2023)
The agricultural sector is the second largest contributor to the PDRB of Padang Pariaman Regency, but the contribution of the agricultural sector to the economy is decreasing. A number of food, horticultural and plantation commodity crops experienced a decline in production from 2016-2020. This study aims to analyze the development, patterns and economic structure of the agricultural sector in Padang Pariaman Regency. This research was conducted in Padang Pariaman Regency, West Sumatra. This study uses 3 agricultural sub-sectors, namely the food crops sub-sector, horticultural crops sub-sector and plantation crops sub-sector. The data used in this research is secondary data consisting of production data. The method used in this research is quantitative. The data sources used in this study came from the Central Bureau of Statistics for Padang Pariaman Regency, the Central Statistics Agency for West Sumatra Province and the Padang Pariaman Regency Agriculture Office in 2016-2020. The data analysis technique used is the Diversity Entropy Index and the Klassen Typology. The results of the study can be concluded that the IDE value for all commodities in the agricultural sub-sector of Padang Pariaman Regency is <1, which means it is not growing or evenly distributed. The results of the Klassen Typology analysis are that there are six commodities that are classified as advanced and fast-growing commodities and fast-growing commodities. There are eight commodities that are classified as advanced but under pressure and commodities that are relatively underdeveloped. Therefore, the government of Padang Pariaman Regency needs to make policies that can support increased activity in the agricultural sector, improve technology and innovation so that productivity increases and commodity equity.